Male Issues of the Ileal Pouch - (:unkn) unknown (LIPPINCOTT WILLIAMS & WILKINS, 2015)
Restorative proctocolectomy with ileal pouch-anal anastomosis is the standard surgical treatment modality for patients with ulcerative colitis who require colectomy. There are special issues related to male gender. We performed systemic literature review on the topic, incorporating the experience in our specialized Center for Ileal Pouch Disorders, and provide recommendations for the identification and management for the gender-specific issues in male patients with ileal pouches. Chronic pouchitis, particularly ischemic pouchitis, anastomotic leak, and presacral sinus are more common in male patients than their female counterparts. Sexual dysfunction can occur after pouch surgery, particularly in those with pouch failure. Diagnosis and management of benign and malignant prostate diseases can be challenging due to the altered pelvic anatomy from the surgery. Digital rectal examination for prostate cancer screening is not reliable. Transpouch biopsy of prostate may lead to pouch fistula or abscess. Pelvic radiation therapy may have an adverse impact on the pouch function. In conclusion, sexual dysfunction and enlarged prostate can occur in patients with the ileal pouch. The measurement of serum prostate-specific antigen is a preferred method for the screening of prostate cancer. If biopsy of the prostate is needed, the perineal route is recommended. The risk for pouch dysfunction and the benefit for oncologic survival of pelvic radiation for prostate cancer should be carefully balanced.
Keywords: gender; inflammatory bowel disease; restorative proctocolectomy; prostate; prostate cancer; sexuality; ulcerative colitis; INFLAMMATORY-BOWEL-DISEASE; QUALITY-OF-LIFE; ULCERATIVE-COLITIS PATIENTS; DYSFUNCTION FOLLOWING PROCTOCOLECTOMY; ANTINEUTROPHIL CYTOPLASMIC ANTIBODY; ANAL ANASTOMOSIS IPAA; PORTAL-VEIN THROMBI; RESTORATIVE PROCTOCOLECTOMY; SEXUAL FUNCTION; CROHNS-DISEASE